Gendered responses to the 2009 Black Saturday bushfires in Victoria, Australia. (10th November 2015) - Whittaker, Joshua; Eriksen, Christine; Haynes, Katharine
Abstract: This paper presents findings from a gendered analysis of resident responses to the 2009 Black Saturday bushfires (wildfires) in Victoria, Australia. One hundred and seventy‐three people lost their lives in the bushfires and more than 2000 houses were destroyed. Previous research on Black Saturday has largely focused on issues of resident preparedness and response, with limited consideration of the role of gender in household decisions and actions. This paper examines the gendered dimensions of risk awareness, preparedness and response among households affected by the bushfires. Data were collected through in‐depth interviews with over 600 survivors and a questionnaire of 1314 households in fire‐affected areas. Analysis revealed that women more often wanted to leave than men, who more often wanted to stay and defend property against the bushfires. Nevertheless, findings suggest that broad‐brush characterisations of staying to defend as a masculine response and leaving as a feminine response are misguided. Although some women expressed a strong desire to leave, others were resolute on staying to defend. Equally, while some men were determined to stay and defend, others had never considered it an option. Despite this, the research identified numerous instances where disagreement had arisen as a result of differing intentions. Conflict most often stemmed from men's reluctance to leave, and was most apparent where households had not adequately planned or discussed their intended responses. The paper concludes by considering the degree to which the findings are consistent with other research on gender and bushfire, and the implications for bushfire safety policy and practice.